Addressing the Challenges Faced by Pakistan’s Healthcare System - Amna Baig; Tayyaba Rahat (Pakistan Journal of Medical Research, 2024)
Pakistan's health system faces a multitude of challenges that are making it hard for people to stay healthy.1 These include  inadequate infrastructure and  a shortage of healthcare professionals.2 However, despite all that, there is hope for a brighter future. This editorial illuminates how Pakistan can pave the way for a more resilient and equitable health system.